Islamic Religious Education Learning Management In Madrasah Aliyah Negeri 3 Tapanuli Tengah - Muhammad Rifai Harahap (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2023)
This paper is entitled Management of Islamic Religious Education Learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah. The problems in this study are how to plan Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah, how to organize Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah, how to implement Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah. Based on the formulation of the problem above, the main objectives of this study are: to determine the planning of Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Central Tapanuli, to determine the organization of Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah, to determine the implementation of Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah, To find out the results of this study, the authors used a qualitative approach by conducting direct interviews with research respondents. The results of the research above can be obtained that the learning management materials for Islamic Religious Education at Madrasah Aliyah Negeri 3 Tapanuli Tengah are classified as good. This can be seen from the results of the author's interviews with research respondents, namely in preparing the Learning Implementation Plan (RPP) respondents have included all learning components, namely basic competencies, indicators, learning objectives, standard materials, learning methods, learning activities, learning resources and assessments. In organizing learning, respondents have tried to use the right method. However, due to limited knowledge about teaching methods, the methods used remain the same. Apart from that, the lack of facilities and infrastructure can hinder the smooth teaching and learning process. The implementation of Islamic Religious Education learning at Madrasah Aliyah Negeri 3 Tapanuli Tengah is generally carried out in class and based on a predetermined schedule.